The Effects of the Opportunity Principle on the Attorney General's Office's Deponerring Implementation - Romula Hasonangan; Hari Purwadi; Andina Elok Puri Maharani (Faculty of Law, Universitas Pekalongan, 2021)
This study aims to analyze the implications of the principle of opportunity for implementing depowering in the Attorney General's Office. This is normative legal research, with secondary data in primary, secondary, and tertiary legal materials. The results showed that implementing depowering as part of the principle of opportunity was not optimal and practical. The causative factors were. First, the legal material was still ambiguous regarding the definition of public interest as the basis for implementing depowering. Secondly, the understanding of the prosecutor's office on the principle of opportunity was not coherent with the principle of equality before the law by the apparatus. Third, the factor of the legal culture of the community whose trust is still deficient in the implementation of the principle of opportunity by the Prosecutor's Office.